1981
DOI: 10.1530/jrf.0.0630499
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous ovum penetration by human spermatozoa

Abstract: Summary. An . Of the 586 ova tested with spermatozoa from the infertile subjects only 11 (1\m=.\9%) showed any evidence of penetration (range of individual penetration rates 0\p=n-\8\m=.\7%) and binding to the vitelline membrane was poor (0 or <5 spermatozoa/ ovum). Spermatozoa from a further 9 infertile men who had abnormal spermiograms also gave poor penetration rates (4/300 ova, 1\m=.\3%). It is concluded that this bioassay has a useful role as an additional test to the classic spermiogram, but that its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…In the donor group the mean penetration rate of 53% coincided with the results of similar groups in different studies where the mean penetration rates in donor and fertile men were 56.3% [14], 54% [6], 55.9% [16], and 59.7% [15]. The mean penetration obtained in this study is low compared with some studies: 81% [19], 69% [ l o ] , and 66% [7].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the donor group the mean penetration rate of 53% coincided with the results of similar groups in different studies where the mean penetration rates in donor and fertile men were 56.3% [14], 54% [6], 55.9% [16], and 59.7% [15]. The mean penetration obtained in this study is low compared with some studies: 81% [19], 69% [ l o ] , and 66% [7].…”
Section: Discussionsupporting
confidence: 86%
“…The range of penetration in this group (11-92%) is also different from that of other investigators: 38-81% [17] and 0 4 . 7 % [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators have found positive correlations between these results, others have failed to do so [5,10,13,19,20,22,261. In the present study the fertile and the infertile subjects differed in both the conventional semen parameters, sperm density and motility, as well as in the in vitro penetrations of hamster ova and bovine cervical mucus.…”
Section: Dlscussionmentioning
confidence: 99%
“…Subject C Within subject variability T h e variation in penetration rates between six different semen samples was studied for 3 individuals and is shown in Table 1 (Tyler et al 1981).…”
Section: Subject Bmentioning
confidence: 99%
“…The results obtained with 15 fertile patients, exhibiting normal sperm concentrations and motility, all showed good sperm attachment and penetration rates of 24-89% (Tyler et al 1981). The HOP test has been performed on the male Relationship between sperm motility in semen and the result of the HOP test in 501 men.…”
Section: Relationship To Other Semen Testsmentioning
confidence: 99%